The kidney reabsorption-related magnesium depletion score is associated with cardiovascular disease and longitudinal mortality in diabetic kidney disease patients - Zhengxi Zhou; Xiaotian Yao (Diabetology & Metabolic Syndrome)
Abstract Background The kidney reabsorption is essential for maintaining magnesium homeostasis. This study aims to explore the relationship between kidney reabsorption-related magnesium depletion score (MDS) and the occurrence of cardiovascular disease (CVD) and prognosis in diabetic disease kidney (DKD) patients. Methods We included 3199 DKD patients from the National Health and Nutrition Examination Survey (NHANES) database, including 1072 CVD patients. Weighted logistic regression analysis was used to explore the relationship between MDS and the occurrence of CVD. Weighted COX proportional hazards regression was used to explore the relationship between MDS and mortality. Stratified analysis was used to further validate. Finally, we assessed the predictive accuracy of MDS on survival outcomes in DKD patients using time-dependent receiver operating characteristic (ROC) curve analysis. Results Survey-weighted multiple logistic regression analysis revealed that MDS ≥ 3, the incidence of CVD increased by 371%. During the follow-up period (median of 87 months), 1373 all-cause deaths (497 cardiovascular deaths) were recorded. In DKD patients, MDS ≥ 3, all-cause mortality increased 78% (P < 0.001) and cardiac mortality 76% (P = 0.08). Consistent results were also shown when stratified by age, sex, race, marital status, magnesium intake. The area under the curve (AUC) values for predicting 1-,2-,3-,4-, and 5-year mortality using MDS were 0.86, 0.66, 0.59, 0.57, and 0.55, for all-cause mortality and 0.9, 0.67, 0.62, 0.58, and 0.56 for cardiovascular mortality. Conclusion MDS, kidney reabsorption-related, is positively correlated with the incidence of CVD and longitudinal mortality in DKD patients.